Drainage of late Wisconsin glacial lakes and the morphology and late quaternary stratigraphy of the New Jersey-southern New England continental shelf and slope - Uchupi, E.; Driscoll, N.; Ballard, R. D.; Bolmer, S. T. (Marine Geology, 2001)
We propose that late Wisconsin deposition and erosion (Hudson Shelf and Block Island valleys) on the shelf and slope from New Jersey to southern New England were a consequence of the catastrophic drainage of glacial lakes behind terminal moraine systems and the huge volume of water stored beneath the Laurentian ice sheet and subsequent erosion of the lake sediments by flash floods. The morphology imparted by glaciation regulated the discharge associated with the ablation of the glaciers. Associated with the deposits west of Hudson Shelf Valley are the remains of mammoth and mastodon which were transported from their living habitats along the lake shores to their present burial sites on the shelf. The floods also triggered gravity flows on the upper continental slope which made possible the transportation of coarse debris over hundreds of km into the deep-sea. That these catastrophic hood morphologies can still be recognized on the middle to outer shelf suggest that much of its surface was little modified during the late Pleistocene/Holocene transgression. Thus the late Pleistocene/Holocene transgression may have been characterized by short periods when sea level rose rapidly allowing for the preservation of relict features. (C) 2001 Elsevier Science B.V. All rights reserved.
400trTimes Cited:50Cited References Count:115